The positivity bias of Chinese temporal collective self: Evidence from the first-person perspective and the third-person perspective - Yue, Caizhen; Long, Yihong; Ni, Chaomei; Wu, Huating; Zhao, Dexuan (Frontiers in Psychology, 2023)
As a unique part of the human thinking, people can project themselves into the past or the future for mental time travel. This study attempts to expand the temporal self into the domain of the collective self. In this study, we adopted an adapted temporal collective self-reference paradigm to explore the positive bias of the temporal collective self. In Experiment 1, the temporal collective self-reference was processed from the first-person perspective, and in Experiment 2, it was processed from the third-person perspective. The results indicated that different temporal collective self showed a certain positive bias from both the first-person perspective and the third-person perspective. People showed the positive bias advantage towards the future collective self to some extent under the first-person perspective, while the positive bias advantage towards the future collective self was disappeared under the third-person perspective. This study suggested that the temporal collective self-representations may be more consistent, unlike the complexity of the individual temporal self-representations. This study contributes to deepen the understanding on the temporal collective self.